Essential Oil Constituents of Seeds and Fresh Leaves of Garden Lettuce (Lactuca sativa L.) Grown in Isfahan, Iran - Suleiman Afsharypuor*; Mahdieh Ranjbar; Mohammad Mazaheri; Fereshteh Shakibaei; Abolfazl Aslani (Iranian Society of Pharmacognosy, 2018)
Background and objectives: Garden lettuce, Lactuca sativa L. (Asteraceae), is an herbaceous plant cultivated in different parts of Iran including Isfahan. In Iranian traditional medicine, it is classified as a medicinal food because it is nutritive and has therapeutic effects. As the therapeutic effects of the plant parts may be related to some volatile active constituents, it was aimed to determine the chemical constituents of the essential oils obtained from seeds and fresh leaves of the plant grown in Isfahan. Methods: Essential oils from seeds and fresh leaves of Lactuca sativa L. were obtained by hydro-distillation method and were analyzed by gas chromatography-mass spectroscopy (GC/MS) method. Results: Identified volatile constituents in the essential oils of the seeds and fresh leaves samples were representing 96.1% and 91.8% of the oils, respectively. Major volatile constituents of the seeds oil were: linoleic acid (38.8%), oleic acid (17.9%), palmitic acid (4.9%), 3-methyl heptane (3.2%), 1-decene (2.8%), 1-hexyl-3-methyl cyclopentane (2.3%), 2,4-decadienal (E,E) (2.2%), limonene (2.1%) and carvone (2.0%). While the main volatile constituents of the fresh leaves oil were: linoleic acid (37.7%), oleic acid (19.6%), palmitic acid (16.7%), 3-methyl heptane (4.6%), 1-ethyl-3-methyl cyclopentane (4.2%), 1-decene (2%), n-octadecane (1.7%) and n-tetradecane (1.5%). Conclusion: Theessential oils from the seeds and fresh leaves of the plant grown in Isfahan mainly composed of a mixture of saturated and unsaturated fatty acids.